2001
DOI: 10.1897/1551-5028(2001)020<2841:sdiass>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Disruption in a Second Species of Wild Cyprinid Fish (The Gudgeon, Gobio Gobio) in United Kingdom Freshwaters

Abstract: To establish whether the intersex condition seen in the roach (Rutilus rutilus) in United Kingdom (UK) rivers was species specific or a more general phenomenon in fish, evidence for sexual disruption was sought in a second cyprinid species, the gudgeon (Gobio gobio). Gudgeon were collected from the Rivers Aire and Lea (at locations that receive high-volume discharges of sewage treatment works [STW] effluent and that contain intersex roach) and from two still waters, and their gonads were examined histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 26 publications
3
92
0
2
Order By: Relevance
“…The GSI values for males determined in this study were similar to those reported by Barnhoorn et al (2004), where the GSI values for intersex catfish collected were in a closer range to the male GSI values than to females. These suggested that the intersex fish could be the result of feminization of male sharptooth catfish, similar to the observation of van Aerle et al (2001) in Gobio gobio specimens collected from rivers in the U.K., downstream of a sewage treatment facility.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The GSI values for males determined in this study were similar to those reported by Barnhoorn et al (2004), where the GSI values for intersex catfish collected were in a closer range to the male GSI values than to females. These suggested that the intersex fish could be the result of feminization of male sharptooth catfish, similar to the observation of van Aerle et al (2001) in Gobio gobio specimens collected from rivers in the U.K., downstream of a sewage treatment facility.…”
Section: Discussionsupporting
confidence: 74%
“…The gonadal somatic index (GSI) was calculated according to the equation: gonadal weight/ (body weight-gonadal weight) Â 100 (van Aerle et al, 2001). The GSI is a somatic index that is frequently used for assessing the health and reproductive status or maturity of fish (De Vlaming, 1981).…”
Section: Collection Of Ugps and Gonadal Tissue In The Fieldmentioning
confidence: 99%
“…In our previous work, we also found that β-estradiol 17-valerate (EV) at 1 ng/L can induce feminization and affect normal development of medaka (Oryzias latipes) (Lei et al, 2013a). Several field studies have also shown that these adverse reproduction and development responses in wild fish may be due to chemicals present in aquatic environments (Van Aerle et al, 2001;Jobling et al, 2006;Lange et al, 2011;Yan et al, 2012) and are related to reproductive failure in fish (Nash et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Estrogens induce vitellogenin, a precursor protein for egg yolk that has been used as a sensitive biomarker for studies of xenoestrogens in aquatic environments (Harries et al 1997;Allen et al 1999aAllen et al , 1999bMinier et al 2000;Simpson et al 2000;Oberdçrster and Cheek 2001;van Aerle et al 2001). We previously found vitellogenin induction and intersex gonads, two bioindicators of the effects of environmental estrogens, in male flounder, Pleuronectes yokohamae, collected from Tokyo Bay, Japan (Hashimoto et al 1998b.…”
mentioning
confidence: 99%